Intermittent claudication caused by a hip joint ganglion - Stanek, F; Ouhrabkova, R; Hejdova, H; Zubkovsky, O; Ott, Z; Kvasnicka, J; Janousek, M (VASA. Zeitschrift fur Gefasskrankheiten, 2007)
A case report of a patient with unusual compressive syndrome is reported herein. A 27-year-old woman was referred to our hospital due to intermittent claudication in the left thigh and calf which gradually developed over the last five months. Angiography showed an atypical short occlusion of the external iliac artery. Only surgical revision made an exact diagnosis. The formation compressing the artery was a ganglion that originated from the hip joint and adhered to the artery. Resection of the ganglion was carried out. The adjacent segment of the artery was removed and replaced by end-to-end venous graft using vena saphena magna. From the operation until present (30 months) the patient remains symptom-free. To our knowledge a hip joint ganglion compressing the artery and causing symptoms of peripheral arterial disease has not been previously reported in medical literature.
Keywords: Ganglion Cysts; Intermittent Claudication; Humans; kyčelní kloub; Treatment Outcome; Arterial Occlusive Diseases; Iliac Artery; lidé; Adult; výsledek terapie; angiografie; arteriální okluzní nemoci; Hip Joint; Female; arteria iliaca; cystická ganglia; vena saphena; dospělí; Saphenous Vein; Tomography, Spiral Computed; tomografie spirální počítačová; Angiography; anastomóza chirurgická; ženské pohlaví; intermitentní klaudikace; Anastomosis, Surgical